Quasi-Static Thermal Stresses in an Infinite Slab - K. Sakaino; A. Atsumi (Engineering Transactions, 1975)
This paper deals with two thermoelastic problems of an infinite slab with or without a cylindrical hole. The thermal stress distribution which arises in a slab if a circular region of the plane boundary (Case A), or a cylindrical boundary (Case B) undergoes a sudden temperature change, is analysed using a thermoelastic potential and a stress function. In both cases, it is considered and graphically shown how the ratio of the radius of the heated circular region, or cylindrical hole, to the plate thickness affects the thermal stress distribution.